The construction and operation of Sarawak river barrage, it's effects on water quality in Sarawak River - Law, Ing Nguong (2001)
This research titled Constructivn and Operation of Sarawak River Barrage, it's Effects on water Quality of Sarawak River is a study on water quality alteration due to the construction and operation of Kuching Barrage located downstream of Sarawak River. The purpose of construction and operation of Kuching Barrage is to control water level at Sarawak River that has a tidal range of 6 m, at the same time serve as a flood mitigation structure. The structure may have serve well in maintaining water quantity, the water quality for Sarawak River has deteriorated. The major water quality problem includes saline intrusion and excessive discharge of domestic and industrial waste into Sarawak River that caused contamination. Longer retention time due to Barrage closure causes reduction of Dissolved Oxygen and multiplication of algal growth that may lead to alga bloom. Secondary monthly water quality data are complied and analysed to determine the level of alteration of water quality. Besides that correlation between different water quality parameters and monthly rainfall are calculated. Primary data are taken to validate the secondary data and determine the alteration along water column. The analysis is to determine the possibility of stratification of water quality at different depth. Hydraulic analysis had been done to calculate discharge during Barrage operation. The discharge is correlated with water level change at different distance from Barrage, saline intrusion and turbulence at surface, mid-depth and riverbed The result of the study shows that it is essential to control the discharge of sewerage directly into Sarawak River and upgrade of sewerage treatment system in Kuching City is vital to secure the water supply for Kuching City. At the same time, there shall have more study to improve the effectiveness of Barrage operation to control saline intrusion.